Prevalence of Inflammatory Back Pain (IBP) In Patients with Backache Visiting Rheumatology OPD at Khyber Teaching Hospital, Peshawar: Inflammatory Back Pain in Patients with Backache - Ali, Amjad; Najibullah, .; Zeb, Alam; Imranullah, .; Khan, Inamullah (Pakistan Journal of Health Sciences, 2024)
Back pain is a prevalent and often paralyzing condition that impacts people of all ages and backgrounds. When it comes to back pain, it is crucial to differentiate between different kinds in order to accurately diagnose and effectively treat the problem. Objective: To ascertain the frequency of Inflammatory Back Pain (IBP) in patients presenting with low back pain. Methods: This descriptive study was conducted in rheumatology department of Khyber Teaching Hospital, Peshawar, during the period 1st September 2023 till 31st March 2024. Male and female patients with back ache (VAS >4) were enrolled and evaluated for the presence of inflammatory back pain using ASAS criteria. Results: The study included 138 patients, 60 (43.48%) male and 78 (56.52%) female. Mean age was 51.7 ± 5.8 years. Majority of the patients belonged to the age group 46 to 60 years 45 (32.60%). The ASAS criteria for IBP was satisfied by 54 (39.1%) patients. Statistically significant association was observed between IBP and family history of IBP. Conclusions: Significant proportion of patients with back pain were found having pain with inflammatory etiology. Male patients aging 46 to 60 years with family history of IBP were more likely having IBP